Volume 5: Engineering Education 2019
DOI: 10.1115/imece2019-10540
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Virtual Lab in Assistance of a Fluid Mechanics Laboratory Instruction

Abstract: Physical laboratory experiments are built to provide students with hands-on opportunities and have long been crucial for engineering training. However, due to the rapid growth in number of enrollments, limited and shared space, undergraduate students have experienced an increasing difficulty gaining valuable hands on experience in the lab. While traditional lab should never be abandoned, adding virtual labs to assist with it could benefit students without the limitation of enrollment capacity or lab availabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A pilot study carried out in the USA in developing a VL relating to fluid mechanics reveal that the virtual tours served as a pre-lab instruction tool and students felt this approach to be very informative and useful. The students also mentioned that the VL pump experiment is intuitive and consumes less time (Zhao et al, 2019). The work carried out at Texas A&M University, USA, shows that the female students spent more time in the VL tutorial (Srinivasa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A pilot study carried out in the USA in developing a VL relating to fluid mechanics reveal that the virtual tours served as a pre-lab instruction tool and students felt this approach to be very informative and useful. The students also mentioned that the VL pump experiment is intuitive and consumes less time (Zhao et al, 2019). The work carried out at Texas A&M University, USA, shows that the female students spent more time in the VL tutorial (Srinivasa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This is because learners now tend to prefer things related to computers [67]. In Zhao et al's study [68], a virtual laboratory was designed to support and enrich the undergraduate learners' laboratory experience in addition to the existing physical laboratory; the learners considered that the virtual laboratory was very informative and useful. Studies [69,70] revealed that the use of virtual laboratory media could improve the learners' conceptual understanding, as well as their problem-solving ability [71], and it enhances their creativity [72].…”
mentioning
confidence: 99%
“…The findings give educators and teachers a thorough grasp of improved learning by state-of-the-art technology to design student-centered learning activities. Zhao et al (2019) stated that students found the virtual tour very informative and useful, whereas the VR pump lab was intuitive and time-saving. This proves that with realistic lab simulations, virtual labs have great potential to give students more flexibility to carry out handson experiments and to develop technical acumen beyond the physical classroom.…”
Section: Discussionmentioning
confidence: 99%